Resistensi dan Potensi Bakteri Indigenous dari Tanah Sekitar Industri Daur Ulang Baterai Aki Terhadap Penurunan Kadar Timbal (Pb) - Yulmaniati Yulmaniati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the resistance and potential of indigenous bacteria from soil around battery recycling industries in reducing lead (Pb) levels. The method used includes bacterial isolation using NA+Pb(NO₃)₂ 100 ppm medium, followed by characterization tests, resistance tests, and lead reduction potential tests. The results showed that 12 bacterial isolates were able to grow on the selection medium. Based on Gram staining and biochemical tests, eight isolates were identified as Bacillus genus, while the other four belonged to the Pseudomonas genus. Resistance tests revealed that six bacterial isolates exhibited lead resistance and potential for heavy metal reduction. Further testing showed that these six isolates could reduce lead levels by up to 99.99%. Keywords: Bioremediation, Battery, Lead, Indigenous Bacteria